Pendugaan Keberadaan Bauksit Laterit di Sebagian Wilayah Gunung Tanjunggangse Menggunakan Metode Geolistrik Tahanan Jenis Konfigurasi Dipol-dipol - Mathali'ul Anwar; Yudha Arman; Muhardi Muhardi (Universitas Muslim Indonesia, 2022)
An estimation of the presence of bauxite in a part of Mount Tanjunggangse, Kendawangan District, Ketapang Regency has been carried out. The geoelectric method of resistivity dipole-dipole configuration with 5 measurements was used to investigate the presence of bauxite later. The length of each measurement is 141 m with a distance between the electrodes of 3 m. The data obtained were processed using the Res2Dinv software. The results showed that the appropriate species boundary values of 279.57 - 6.552 Ωm were interpreted as bauxite, a value of 6.552 - 25.172 Ωm was interpreted as saprolite, and a value of 25.172 - 161.244 Ωm was interpreted as sandstone.